Dealing with Non-Convexity in Geographic Routing in Smart Dust Networks - Kłopotek, Mieczysław; Ruciński, Dariusz; Tchórzewski, Jerzy (Studia Informatica. System and information technology, 2006)
The paper proposes a new approach to greedy geographic routing for sensor networks with non-convex covering structure.